The relationship between working capital management, solvency, profitability and bankruptcy risk: case of property and real estate sub-sector in indonesia capital market - Arira Putri, Rizkita; Murtaqi, Isrochmani (The Indonesian Journal of Business Administration, 2019)
Abstract. Bankruptcy becomes a major risk faced by every companies including property and real estate companies in Indonesia. Currently, some economic and business analysts conclude that Indonesia's property sector still has a decline trend in 2018. Bankruptcy is not always experienced by poor performance companies, but it can also be experienced by companies with strong performance. Performance of the company can be affected by the efficiency of companies’ working capital management. That can be the reason why thorough bankruptcy assessment will be needed. The purpose of this study is to examine the relationship between bankruptcy risk (Altman Z-Score) of property and real estate companies in Indonesia and the efficiency of working capital management, solvency, and profitability. The study focuses on 41 publicly-listed firms of property and real estate sub-sectors in Indonesia Stock Exchange during the period of 2012-2017. Bankruptcy risk calculation will be examined based on Altman Bankruptcy Theory. Besides, the components Cash Conversion Cycle wll be used as working capital management indicator, DAR as the solvency indicator, and ROE as the profitability indicator. The relationship between bankruptcy risk and the efficiency of working capital management, solvency, and profitability will be examined using panel data regression method. The result of this study indicates that AAI, APP, and ROE are significantly related to bankruptcy risk (Altman Z-Score). The study will contribute as an empirical analysis to highlight the link relationship between working capital management efficiency, solvency and profitability with bankruptcy risk of property and real estate companies in Indonesia.Keywords: Altman Bankruptcy Model, Bankruptcy Risk, Working Capital Management, Cash Conversion Cycle, Property and Real Estate.